Review on the Performances of Cihateup Duck (Anas platyrhynchos Javanica) as Genetic Resource of Local Poultry in Indonesia - Matitaputty, Procula R; ., Suryana (Indonesian Animal Sciences Society, 2014)
Cihateup duck is one of the local Indonesian poultry genetic resources originated from West Java. These ducks are raised in Tasikmalaya and its surrounding area. Cihateup duck raised as layer or meat type duck is potential to provide business opportunities for people in West Java. For future development of Cihateup duck, some important potential characteristics of Cihateup ducks are required. This paper describes the phenotype performance, rearing management of Cihateup ducks and its genetic relationship with other ducks. Cihateup ducks have longer neck, wing, femur and tibia compared with other Indonesian ducks. Egg production (200 egg/head/year) is lower than Alabio and Mojosari ducks. The quality of meat (taste and flavour) is less preferred by consumers because of its odor. Genetic relationship between Cihateup duck with local ducks in Java is closer than Alabio ducks from South Kalimantan. Key words: Cihateup duck, performance, genetic resource